Effect of oxetanocin G, a novel nucleoside analog, on DNA synthesis by hepatitis B virus virions. - Nagahata, T (1994)
The novel nucleoside oxetanocin G, 9-(2-deoxy-2-hydroxymethyl-beta-D-erythro-oxetanosyl)guanine (OXT-G), that is a derivative of oxetanocin A, was studied in relation to its action on the synthesis of hepatitis B virus (HBV) DNA and cellular DNA in an HBV-producing cell line, HB611 (T. Tsurimoto, A. Fujiyama, and K. Matsubara, Proc. Natl. Acad. Sci. USA 84:444-448, 1987). The median effective concentration of OXT-G against HBV replication was 1.5 microM, and the median cytotoxic concentration was more than 1,000 microM. At the same concentration, OXT-G did not inhibit cellular DNA synthesis or viral RNA synthesis. Chemically synthesized OXT-GTP inhibited the HBV endogenous DNA polymerase reaction and was incorporated into HBV DNA strands at a low efficiency compared with the incorporation of dGTP. A synthetic primer-template study revealed that OXT-GTP was incorporated into DNA strands at a low efficiency and that further extension of the DNA strand by using the 2' position of the incorporated OXT-G could take place.